Halloysite nanotubes-enhanced epoxy acrylate latex emulsion as a novel anticorrosive protective coating for metal surface in 3.5% NaCl solution - Asif, Muhammad; Ahmad, Matloob; Saif, Muhammad Jawwad; Anjum, Muhammad Naveed; Zaki, Magdi E. A. (Frontiers in Chemistry, 2024)
Corrosion is a major problem that can lead to the degradation of metal structures. In this study, we developed a novel corrosion-protective coating for metal substrates based on a modified epoxy acrylate formulation reinforced with halloysite nanotubes (HNTs). Epoxy acrylate oligomers were first synthesized through the acrylation of epoxy using acrylic acid, followed by copolymerization with butyl methacrylate/vinyl acetate monomers to produce grafted epoxy acrylates (GEA). HNTs were then incorporated into the polymeric dispersion at weight loadings of 1%, 1.5%, and 2%. The corrosion resistance and waterproofing properties of the coatings were evaluated. The results showed that steel samples coated with HNTs-modified GEA showed no signs of rusting even after 16 days of immersion in a corrosive solution, whereas those coated with GEA alone showed rusting after only 9 days. These results demonstrate the effectiveness of HNTs-modified GEA coatings in protecting steel surfaces against corrosion. The coatings are also water-resistant and can be easily applied. This work provides a new approach to developing corrosion-protective coatings for metal substrates.